PUSH NET (WAN RUM) SERTA DAMPAKNYA PADA KEHIDUPAN SOSIAL EKONOMI NELAYAN (KASUS KAMPUNG RU SEMBILAN, THAILAND SELATAN) - Ali, Surmiati (P2KK LIPI, 2006)
This article discusses the influence of modern technology of fishing over the social life in a Muslim fishing community in South Thailand or Pattani. The advent of modern fishing technology to peoples fishing ground raises some problems in traditional fisher in Ru sembilan. Firstly, there is a drastically decreasing resource in fishing ground, so that they face difficulties in finding catchers. Secondly, their commercial access to fishing ground raises a conflict among them drives to financial lost. This paper also explains the Thailand government policy in handling fisher conflict to management and conservation on aquatic resources. It seems that the Thailand Monarchic Government is considered discriminate local fisher. When people stop using dangerous catching instrument, in other hands commercial fishers keep operating in their fishing ground. It cause the conflict dragging continuously. It is not only because of poverty, but the traditional fisher can not going to work off shore. Keywords: Nelayan; Konflik; Alat tangkap; Kesejahteraan